Role of Gamma Interferon and Interleukin-4 in Host Defense against the Human Filarial Parasite Brugia malayi - Babu, Subash (American Society for Microbiology, 2000)
We have investigated the roles of gamma interferon (IFN-γ) and interleukin-4 (IL-4) in host defense against Brugia malayi. Our data suggest that the lack of either IFN-γ or IL-4 prolongs the time required to achieve sterile immunity, suggesting that both canonical type 1 and type 2 responses are involved in the clearance of infection.